Rare Occurrence of Prostate Cancer Metastasizing to the Orbit: A Case Report - S, Praveena; K, Vinay; Chalimidi, Karunakar Reddy; T, Krishna Prasad (Medical Journal of Shree Birendra Hospital, 2022)
Prostate cancer is second most common cancer with frequent metastasis occurring to bone. We report a unique case of soft tissue and bony orbital metastasis from carcinoma prostate. The patient presented with orbital metastasis after defaulting to the advised treatment. He responded well to radiation therapy and the lesion regressed completely. Our patient was diagnosed to have an oligo-metastatic carcinoma of the prostate. He was non-compliant with treatment and presented to us with proptosis, which was later diagnosed to be an orbital metastasis from prostate cancer. It responded well to the external beam chemotherapy. Orbital metastasis is a rare but known complication of carcinoma prostate. One must consider the diagnosis of orbital metastasis from carcinoma prostate in an elderly male presenting with proptosis.